CLINICAL ISOLATES OF STAPHYLOCOCCUS AUREUS (R.): BIOFILM CHARACTERISATION AND INHIBITORY ASSAY USING HAMAMELIS VIRGINIANA (L.). - CAROL PEREIRA,; PAVITHRA NIRANJAN,; R.MANIKANTAN, (International Journal of Pharma and Bio Sciences, 2014)
In this study, 75 clinical isolates of Staphylococcus species which included 45 isolates of S.aureus and 30 isolates of other Staphylococcus species were initially screened for biofilm production. The prevalence of Multidrug Resistant Staphylococcus aureus (MDRSA) and its biofilm production efficacy was assayed.Further biofilm inhibition using Hamamelis virginiana (Witch Hazel) extract was analysed. The findings showed that the clinical isolates are multidrug resistant. Antibacterial activity of Hamamelis virginiana (Witch Hazel) extract has been proved in this study . The infections caused by Staphylococcus aureus can be minimized by using this extract formulation as an alternative treatment instead of antibiotics. The minimum inhibitory concentration (MIC) was found to be at 10-6 dilution (0.0001µl/ml) of Hamamelis virginiana extract against Staphylococcus aureus. From various experiments, the inhibitory activity of Hamamelis virginiana extract was proved and from the recorded results, the potential use of the extract as an inhibitory agent in controlling Staphyloccocal infections is suggested.